1999
DOI: 10.1046/j.1365-2869.1999.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the performance impairment associated with fatigue

Abstract: SUMMARYThe present study systematically compared the effects of fatigue and alcohol intoxication on a range of neurobehavioural tasks. By doing so, it was possible to quantify the performance impairment associated with fatigue and express it as a blood alcohol impairment equivalent. Twenty-two healthy subjects aged 19-26 years participated in three counterbalanced conditions. In the sustained wakefulness condition, subjects were kept awake for 28 h. In the alcohol and placebo conditions, subjects consumed eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(103 citation statements)
references
References 23 publications
4
94
0
2
Order By: Relevance
“…Prolonged microepisodes of sleep during driving considerably reduce the driving safety [59]. With regard to such parameters as the concentration of attention, reflexes, perceptiveness and accuracy of task performance, the effects of a 24-hour sleep deprivation, or of a 4-5-hour night sleep repeated over a period of one week, are similar to those induced by the 0.5-1‰ level of blood alcohol concentration [153][154][155][156][157]. In most of the European countries, the highest permissible blood level of alcohol in car drivers is 0.5‰, and the Polish law permits only the values below 0.2‰.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Prolonged microepisodes of sleep during driving considerably reduce the driving safety [59]. With regard to such parameters as the concentration of attention, reflexes, perceptiveness and accuracy of task performance, the effects of a 24-hour sleep deprivation, or of a 4-5-hour night sleep repeated over a period of one week, are similar to those induced by the 0.5-1‰ level of blood alcohol concentration [153][154][155][156][157]. In most of the European countries, the highest permissible blood level of alcohol in car drivers is 0.5‰, and the Polish law permits only the values below 0.2‰.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The experimental protocol was specifically chosen to produce measurable and meaningful levels of impairment in participants (as based on Lamond & Dawson, 1999). Furthermore, this protocol was also run using dim light and no social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol reflected that used by Lamond and Dawson (1999), mentioned above, in order to ensure that the participants reached levels of fatigue that were measurable and meaningful. That is, after remaining awake for a single night (20-24 consecutive hours), participants in this study demonstrated levels of performance impairment that were equivalent to someone with a BAC twice the legal driving limit in Australia (0.10% BAC).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it now appears that overly-tired aviators may face operational risks similar to those posed by alcohol intoxication. Recent studies have established that from 17-25 hours of sustained wakefulness can produce an array of performance deficits equivalent to those observed with blood alcohol concentrations (BAC's) of 0.05% to 0.10%--the legal limits for driver intoxication (Dawson and Reid, 1997;Lamond and Dawson, 1999).…”
Section: Introductionmentioning
confidence: 99%